Selection signature analysis and genome-wide divergence of South African Merino breeds from their founders - Dzomba, E. F.; Van Der Nest, M. A.; Mthembu, J. N. T.; Soma, P; Snyman, M. A.; Chimonyo, M.; Muchadeyi, F. C. (Frontiers in Genetics, 2023)
Merino sheep are a breed of choice across the world popularly kept for their wool and mutton value. This study evaluated genetic diversity, population structure and breed divergence in 279 animals of Merino and Merino-based sheep breeds of South Africa using the Illumina Ovine50K BeadChip. The sheep breeds analysed included the three Merino-derived breeds of Dohne Merino ; Meatmaster and Afrino and five presumed ancestral populations of Merinos (Merino ; South African Merino and South African Mutton Merino) and non-Merino founding breeds of Damara , Ronderib Afrikaner and Nguni. Highest genetic diversity values were observed in Dohne Merino (DM) with Ho = 0.39±0.01 followed by Meatmaster and South African Merino (SAM) with Ho = 0.37±0.03. The level of inbreeding ranged from 0.0±0.02 (DM) to 0.27±0.05 (Nguni). Analysis of Molecular Variance (AMOVA) showed high within population variance (>80%) across all population categories. The first Principal Component (PC1) separated the Merino, South African Mutton Merino (SAMM), DM and Afrino (AFR) from the Meatmaster, Damara, Nguni and Ronderib Afrikaner (RDA). PC2 aligned each Merino derived breed with its presumed ancestors and separated the SAMM from the Merino and SAM. The |iHS| analysis yielded selection sweeps across the AFR (12 sweeps), Meatmaster (4 sweeps) and DM (29 sweeps). Genes associated with hair/wool traits such as FGF12, metabolic genes of ICA1, NXPH1 and GPR171 and immune response genes of IL22 IL26, IFNAR1 and IL10RB were reported. The DM vs SAMM shared all six sweeps regions on chromosomes 1, 10 and 11 with AFR vs SAMM. Genes such as FGF12 on OAR 1:191,3-194,7Mb and MAP2K4 on OAR11:28,6-31,3Mb were observed. The selection sweep on chromosome 10 region 28,6-30,3 Mb harbouring the RXFP2 for polledness was shared between DM vs Merino, Meatmaster vs Merino and Meatmaster vs Nguni. The DM vs Merino and the Meatmaster vs Merino also shared an Rsb-based selection sweep on chromosome 1 region 268,5 - 269,9 Mb associated with the Calpain gene, CAPN7. Overall, the study demonstrated some genetic similarities between the Merino and Merino-derived breeds emanating from common founding populations and some divergence driven by breed-specific selection goals.